Tradisi Pembacaan Sholawat Wahidiyah Keliling Sebagai Metode Pendekatan Diri Kepada Allah SWT Di Desa Gardu - Didit Ruhdiyanto; Reynaldi Aldiansyah; Nabila Aufa Salsabila; Silmi Niswa Maulida; Afif Nurseha; N. Maemunah; Roni Roni (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
This research was conducted in Gardu Village, Kiarapedes District, Purwakarta Regency, because in this village the practitioners practice sholawat wahidiyah. They routinely carry out mujadah activities (reading sholawat wahidiyah prayers and practicing them). In everyday life, people who practice sholawat wahidiyah also uphold ethical values in social relations. The type of research that will be carried out by researchers is a type of field research, namely by making direct observations in the field with qualitative methods. The form of activity carried out by Sholawat practitioners is the Usbuiyah mujahadah (mujahadah which is carried out once a week). While the social ethics contained in the Teachings of Sholawat Wahidiyah, namely in this teaching besides humans are taught to always increase faith, Islam, and ihsan so as to form akhlaqul karimah. Humans are also taught to relate well to fellow creatures of God, both to fellow humans (society and the surrounding environment) and to the universe.